Listeria Monocytogenes Presence in Milk and Dairy Products - Hind Salim Abdzed; Assist. Prof. Dr. Kadhim Saleh Kadhim; Assist. Prof. Dr. Mohammed Assad Saleh (Scientific Trends, 2022)
The objective of the present study was to detection of Listeria monocytogenes. In raw milk and dairy products. two hundred fifty Samples of milk and dairy products which include (yogurt, cheese, Butter) were collected randomly in interval from January to Mars 2022, in Karbala province, the samples of milk have been collected from cows in local farms while the samples of dairy products were collected from markets and sail points, then the samples were processed according to standard protocols of Listeria monocytogenes and delivered to laboratory for analyzed. the study of physical features for the samples of milk and dairy products which contaminated with L.M have been revealed change in color, smell and taste, while the biochemical reactions have been showed decrease in PH, increase in chloride while catalase and WST were given positive reaction. the bacteriological study which included isolation and identification of listeria monocytogenes from animal sources by using selective media for listeria monocytogenes, oxford agar (hi media) for culturing. The isolates of L.M have revealed as black colonies also all isolates of L.M were given positive results for catalase test. molecular study of L. Monocytogenes was done by conventional PCR technique after DNA extraction using a DNA extraction Kit. four specific multiplex primers (Hyl-1-f, Hyl-2-R, List-F, List-R) were designed on the basis of a divergent region of the L. monocytogenes genome that was by means of microarray analysis directed to the hly gene, isolates of L. Monocytogenes were identified and study of genetic variation between local listeria monocytogenes isolates which was carried out using the DNA sequencing process which confirming contamination of raw milk and dairy products samples. L.M were reveled highly sensitivity (62.50%) to PCR than culture while the specificity (95.24%) have been showed high in culture than PCR.
Keywords: Listeria Monocytogenes, Raw milk, Dairy products contamination.